P-Cadherin Linking Breast Cancer Stem Cells and Invasion: A Promising Marker to Identify an “Intermediate/Metastable” EMT State - Ribeiro, Ana Sofia; Paredes, Joana (Frontiers in Oncology, 2015)
Epithelial–mesenchymal transition (also known as EMT) is a fundamental mechanism occurring during embryonic development and tissue differentiation, being also crucial for cancer progression. Actually, the EMT program contributes to the dissemination of cancer cells from solid tumors and to the formation of micro-metastasis that subsequently develop into clinically detectable metastases. Besides being a process that is defined by the progressive loss of epithelial cell characteristics and the acquisition of mesenchymal features, EMT has also been implicated in therapy resistance, immune escape, and maintenance of cancer stem cell properties, such as self-renewal capacity. However, the majority of the studies usually neglect the progressive alterations occurring during intermediate EMT states, which imply a range of phenotypic cellular heterogeneity that can potentially generate more metastable and plastic tumor cells. In fact, few studies have tried to identify these transitory states, partly due to the current lack of a detailed understanding of EMT, as well as of reliable readouts for its progression. Herein, a brief review of evidences is presented, showing that P-cadherin expression, which has been already identified as a breast cancer stem cell marker and invasive promoter, is probably able to identify an intermediate EMT state associated with a metastable phenotype. This hypothesis is based on our own work, as well as on the results described by others, which suggest the use of P-cadherin as a promising EMT marker, clearly functioning as an important clinical prognostic factor and putative therapeutic target in breast carcinogenesis.